Important Aspects of Organizing The Activities of Local Representative Bodies of State Authorities Based on The Principle of "Strong Kengash, Accountable And Initiative Khokim" - Bakhtiyar, Torebekov (Jurnal Teknologi Pendidikan, 2025)
This article examines key aspects of the functioning of local representative bodies of state power in the context of the principle of "Strong Kengash, accountable and proactive khokim". The main attention is paid to local representative bodies of state power, their structure, mechanisms of interaction with the executive power and tools for increasing their effectiveness. The study uses methods of comparative analysis, systems approach, as well as studying the regulatory framework governing the activities of local representative bodies. An analysis of the best practices for organizing their work is carried out, taking into account modern requirements for local management. The results of the study allow us to identify key areas for improving the activities of local representative bodies, as well as to offer recommendations for increasing their effectiveness within the framework of the principle under consideration.